New Insights Into Interactions of Presynaptic Calcium Channel Subtypes and SNARE Proteins in Neurotransmitter Release - He, Rongfang; Zhang, Juan; Yu, Yiyan; Jizi, Laluo; Wang, Weizhong; Li, Miaoling (Frontiers in Molecular Neuroscience, 2018)
Action potential（AP） induces presynaptic membrane depolarization and subsequent opening of Ca2+ channels, and then triggers neurotransmitter release at the active zone of presynaptic terminal. Interactions of presynaptic Ca2+channels and SNARE proteins (SNAREs) form a large signal transfer complex, which are core components for exocytosis. Ca2+ channels via directly binding and indirectly activating of active zone proteins and SNAREs serve to regulate the activity of Ca2+ channels. The activation of Ca2+ channels promotes synaptic vesicle recruitment, docking, priming, fusion and neurotransmission release. Intracellular calcium increase is a key step for the initiation of vesicle fusion. Various voltage-gated calcium channel (VGCC) subtypes exert different physiological functions. Up to now, it is still not clear how the different subtypes of calcium channels integrally regulate neurotransmitters release within 200µs of the AP arriving at the active zone of synaptic terminal. In this review, we provide a brief overview for the structure and physiological function of Ca2+ channel subtypes, interactions of Ca2+ channels and SNAREs in neurotransmitter release, and dynamic fine-tune Ca2+ channel activities by G proteins (Gβγ), multiple protein kinases, and Ca2+ sensor (CaS) proteins.